2020
DOI: 10.1021/acs.jpcb.0c06258
|View full text |Cite
|
Sign up to set email alerts
|

NMR Intermolecular Dipolar Cross-Relaxation in Nanoconfined Fluids

Abstract: Spin relaxation, a defining mechanism of nuclear magnetic resonance (NMR), has been a prime method for determining three-dimensional molecular structures and their dynamics in solution. It also plays key roles for contrast enhancement in magnetic resonance imaging (MRI). In bulk solutions, rapid Brownian molecular diffusion modulates dipolar interactions between a spin pair from different molecules, resulting in very weak intermolecular relaxations. We show that in fluids confined in nanospace or nanopores (na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 32 publications
(71 reference statements)
2
10
0
Order By: Relevance
“…The drastically different behaviors between materials at the nano scale and ones at the bulk scale are well documented and can be related to the boundary conditions at nanometer or bulk scales . We have observed that intermolecular cross-relaxation in nanofluidics were enhanced by two orders of magnitude as a result of nanoconfinement on the molecular translational diffusion . Here, we further show how nanoconfinement of the fluids enhances the dipolar cross-relaxation between the fluid and the matrix solids.…”
Section: Introductionsupporting
confidence: 52%
See 2 more Smart Citations
“…The drastically different behaviors between materials at the nano scale and ones at the bulk scale are well documented and can be related to the boundary conditions at nanometer or bulk scales . We have observed that intermolecular cross-relaxation in nanofluidics were enhanced by two orders of magnitude as a result of nanoconfinement on the molecular translational diffusion . Here, we further show how nanoconfinement of the fluids enhances the dipolar cross-relaxation between the fluid and the matrix solids.…”
Section: Introductionsupporting
confidence: 52%
“…In the 2D NOESY spectrum of Figure b, the cross peaks between CH 3 OD and MCM41-C1 are positive, which is the opposite result that would be generally observed in a bulk solution where the cross peaks are negative from positive intermolecular cross-relaxation rates . In addition, the cross peaks in Figure b are strong in comparison to the diagonal peaks, in contrast to the generally weak cross peaks of intermolecular NOEs in bulk fluids with fast molecular tumbling. , …”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…In the 2D NOESY spectra of Figure 1b, the cross peaks between CH3OD and MCM41-C1 are positive, which is the opposite results that would be generally observed in a bulk solution where the cross peaks are negative from positive intermolecular cross-relaxation rates 43 . In addition, the cross peaks in Figure 1b are strong in comparison to the diagonal peaks, in contrast to the generally weak cross peaks of intermolecular NOEs in bulk fluids with fast molecular tumbling 30,43 .…”
Section: Nanoconfinement Enhance the Interaction Of Confined Fluids W...mentioning
confidence: 84%
“…We have observed that intermolecular cross-relaxation in nanofluidics were enhanced by two order of magnitudes as a result of nanoconfinement on the molecular translational diffusion 30 . We establish a formal theory and experimentally show how nanoconfinement of the fluids enhances the dipolar cross-relaxation between the fluid and the matrix solids.…”
Section: Introductionmentioning
confidence: 93%